Balanced Cluster Head Selection Based on Modified -Means in a Distributed Wireless Sensor Network - Sasikumar Periyasamy; Sibaram Khara; Shankar Thangavelu (International Journal of Distributed Sensor Networks)
A major problem with Wireless Sensor Networks (WSNs) is the maximization of effective network lifetime through minimization of energy usage in the network nodes. A modified k -means ( Mk- means) algorithm for clustering was proposed which includes three cluster heads (simultaneously chosen) for each cluster. These cluster heads (CHs) use a load sharing mechanism to rotate as the active cluster head, which conserves residual energy of the nodes, thereby extending network lifetime. Moreover, it reduces the number of times reclustering has to be done and significantly increases the number of data packets sent during network operation. The results show that Mk- means (modified k -means) algorithm was found to outperform the existing clustering algorithms owing to its unique multiple cluster head methodology.